Subsidy Removal, Corrupt Practices and Implications on the Nigerian Economy, 2012-2023 - Adebogun, Olayinka Babatunde; Olatunji, Oduntan Joseph; Agboola, Olugbenga A. Agboola; Edeh, Abraham (African Journal of Stability and Development (AJSD), 2024)
Subsidy removal and corruption significantly impact the Nigerian economy. This study investigates the impact of subsidy removal and corruption on the Nigerian economy from 2012 to 2023. The main objective is to analyse the economic consequences of subsidy removal policies and the types and forms of corruption associated with them. The study adopted the Public Choice Theory as the theoretical framework for understanding the decision-making processes and behaviour of stakeholders involved in subsidy removal and corruption. Methodologically, the study employs a qualitative approach, using secondary data, analysed through content and historical analysis. Findings indicate that while subsidy removal policies aim for fiscal sustainability, they often lead to inflationary pressures, social unrest, and public dissatisfaction. Moreover, corruption exacerbates these challenges, undermining governance, transparency, and accountability. Based on the findings, the study recommends strengthening anti-corruption measures, enhancing governance and institutional capacity, implementing targeted social safety nets, fostering public-private partnerships, and enhancing international cooperation to address the challenges posed by subsidy removal and corruption. These recommendations aim to promote transparency, accountability, and inclusive economic development in Nigeria. Overall, this study contributes empirical evidence, theoretical insights, and policy recommendations for understanding and addressing the complex interactions between subsidy policies, corruption dynamics, and socio-economic development in Nigeria.